A comparison across ranks of well-being among police officers in Malaysia - Md. Yassin, Sulaiman; Rodriguez, Adriana Maria Ortega; Alby, Jeffrey Lawrence D'Silva; Abu Samah, Asnarulkhadi; Omar, Siti Zobidah (Canadian Center of Science and Education, 2016)
Objective: This paper aimed to determine the level of well-being of Police officers and to assess and compare the well-being levels among police officers of low, middle and high ranks. Methods: Data were obtained using a context specific questionnaire that was distributed across the five geographic zones of Malaysia. Results: The results indicate that overall police officers’ well-being is in need of improvement. Low rank officers faced poor work environment, deficient financial security and economic well-being, lack of opportunity for continuing education and career, poor overall physical health and negative political and spiritual well-being. The finding of this study provides the necessary information to develop and implement measures to enhance the current well-being of police officers.